Antibacterial, Antibiofilm, and Antischistosomal Activity of Montrichardia linifera (Arruda) Schott (Araceae) Leaf Extracts - Cleiane Lima; Dallyla Andrade; Gleidiany Moreira; Ângelo Sousa; Antonia Leal; Juliana Figuerêdo; Pedro Furtado; Chistiane Feitosa; Alyne Araujo; Ivanilza Andrade; João Miranda; Aldilene Lima; et al. (Scientia Pharmaceutica, 2021)
With a broad ethnopharmacological tradition in Brazil, Montrichardia linifera has been reported as a potent antirheumatic, antimicrobial, and antiprotozoan agent. However, there is a lack of studies on its effect on bacterial biofilm formation and Schistosoma mansoni worms. This study reports the effects of antibacterial, antibiofilm, and antischistosomal properties of leaf extracts of M. linifera. Phytochemical screening and identification of the main compounds of the extracts were performed. All the extracts evaluated showed antibacterial activity at the concentrations tested. We checked for the presence of flavonoids and derivatives of phenolic acids by the presence of spectra with bands characteristic of these classes in the sample analyzed. The antibacterial assays showed that the best MICs corresponded to 125 µg/mL against Enterococcus faecalis ATCC 29212 in all fractions. The ethanolic and methanolic extracts showed the ability to inhibit biofilm of Staphylococcus aureus ATCC 25123. For the antischistosomal activity, only the acetone and ethyl acetate extracts had a significant effect against helminths, with potent activity at a concentration of 50 µg/mL, killing 100% of the worms after 72 h of incubation. The M. linifera leaf extracts showed antibacterial activity, biofilm inhibition capacity, and anthelmintic activity against S. mansoni.